Proposta de complementação aos requisitos da Resolução da Diretoria Colegiada nº 59/2000 da Anvisa, com base no modelo de gestão da Fundação Nacional da Qualidade e nas necessidades de uma empresa da área da saúde. - Barboza, Luciano Ferreira (2012)
The aim of this study was to identify the differences between the standard RDC 59/2000, of the Brazilian National Sanitary Surveillance Agency (Anvisa) and the Excellence Model of Management of the National Quality Foundation (FNQ), proposing a necessary complement to the implantation of a Management System Quality effective, that considers the needs of a company in the field of health case study. The study used a methodology that, according to their order, covered both applied researches, as interventionist, and regarding their means of investigation was used a field survey, documentary, bibliographic and case study. In conclusion appears to complement the requirements of the standard RDC 59/2000 in order to provide the reference model, the most comprehensive business management model to considerate the needs of the company case study, ensuring that this is an adequate way to cover identified gaps.